MELEJITKAN SELF-CONCEPT PESERTA DIDIK MELALUI VIRTUAL REALITY (VR) DENGAN PROBLEM BASED LEARNING INVESTIGASI TEMPE - Fiantika, Feny Rita; Fanani, Achmad; Prayitno, Sunyoto Hadi; Fauziyah, Nur (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2024)
21st century education requires students to be able to develop various competenciew that not only include cognitive aspects, but also non-cognitive aspects such as attitudes, values and social skills. One inovative approach in developing assessment instruments is through the application of ecomath using Virtual Reality (VR) technology. Ecomath is packaged in market content presented in VR to stimulate students in learning mathematics. Problem based learning is used to boost students’ self-concept and problem solving abilities. This research is a qualitative descriptive study, which describes the results of implementing lesson study with the stages of plan, do, and see. The instruments used in this research were tests and observations. The research results showed an increase in self-concept and the ability to express between concepts by up to 21% in 2 cycles. Furthermore, VR can be used to stimulate students in learning economics with PjBL to increase insight and knowledge in meaningful learning.